EhVps23, an ESCRT-I Member, Is a Key Factor in Secretion, Motility, Phagocytosis and Tissue Invasion by Entamoeba histolytica - Galindo, Ausencio; Javier-Reyna, Rosario; García-Rivera, Guillermina; Bañuelos, Cecilia; Chávez-Munguía, Bibiana; Salazar-Villatoro, Lizbeth; Orozco, Esther (Frontiers in Cellular and Infection Microbiology, 2022)
The EhVps23 protein, an orthologue of the yeast Vps23 and the mammalian TSG101 proteins, is the single member of the ESCRT-I complex of Entamoeba histolytica detected until now. EhVps23 participates in vesicular trafficking, which influences several cellular functions. In this paper, we investigated the role of EhVps23 in virulence-related functions, including the invasive capacity of the trophozoites. Trophozoites overexpressing the EhVps23 protein (Neo-EhVps23) presented helical arrangements in the cytoplasm, similar to the ones formed by EhVps32 for vesicle scission, where EhVps23 was located. By confocal and transmission electron microscopy, EhVps23 was detected in multivesicular bodies, vesicles, and the extracellular space. It was also secreted in exosome-like vesicles together with other proteins, including the EhADH adhesin. Probably, these vesicles carry molecules that participate in the prey capture or in cell-cell communication. Mass spectrometry of precipitates obtained using α-EhVps23 antibodies, evidenced the presence of proteins involved in motility, phagocytosis, vesicular trafficking, and secretion. The study of cellular functions, revealed that Neo-EhVps23 trophozoites exhibit characteristics similar to those described for mammalian transformed cells: they grew 50% faster than the control; presented a significantly higher rate of phagocytosis, and migrated five-fold faster than the control, in concordance with the low rate of migration exhibited by Ehvps23-knocked down trophozoites. In addition, Neo-EhVps23 trophozoites produced dramatic liver abscesses in experimental animals. In conclusion, our results showed that EhVps23 overexpression gave to the trophozoites characteristics that resemble cancer cells, such as increased cell proliferation, migration, and invasion.